2022
DOI: 10.1039/d2bm00803c
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional theranostics nanosystem featuring self-assembly of alcohol-abuse drug and photosensitizers for synergistic cancer therapy

Abstract: Conventional treatments for cancer include chemotherapy, surgical resection, radiotherapy have shown limited therapeutic efficacy, such as severe side effects, lack of targeting and drug resistance of monotherapy were limited to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…According to the report, different EDCI/NHS and buffer systems were considered [35][36][37][38][39]. It was found that when the ratio of NHS to EDCI exceeded one, there was almost no unreacted adenine and thymine.…”
Section: Preparation Of Cmc-at Nanofiber Hydrogel Adhesivementioning
confidence: 99%
“…According to the report, different EDCI/NHS and buffer systems were considered [35][36][37][38][39]. It was found that when the ratio of NHS to EDCI exceeded one, there was almost no unreacted adenine and thymine.…”
Section: Preparation Of Cmc-at Nanofiber Hydrogel Adhesivementioning
confidence: 99%
“…Santhamoorthy et al prepared a double-pH and thermosensitive copolymer hydrogel (HG) system (PNIPAm-co-PAAm HG) using N-isopropylacrylamide (NIPAm) and acrylamide (AAm) as comonomers [77]. Wu et al developed a dual-targeted nanoscale drug delivery system based on EpCAM aptamers and lactic acid-modified oligoamide amine dendrimers for the simultaneous delivery of the FDA-approved drug disulfiram and the photosensitizer indocyanine green, thereby realizing a system that combined imaging and therapeutic functions in a single platform [78]. Wu et al also prepared a dual-gated folate functionalized nanodiamond delivery system (NPFSSD), which exhibited activated fluorescence and cytotoxicity for doxorubicin [79].…”
Section: Research Progress On Dual-drug-delivery Nano-theranostic Age...mentioning
confidence: 99%
“…Chemotherapy is currently the primary and most successful mode of tumor therapy in the clinic. 3 In this context, phototherapies like photodynamic treatment (PDT) and photothermal treatment (PTT) have visible encouraging outcomes in the treatment of cancer. Treatment methods that integrate laser light with photosensitizers (PSs) provide great spatial-temporal controllability, low invasiveness, and little medication resistance.…”
Section: Introductionmentioning
confidence: 99%